PKM peraturan futsal Mahasiswa FIK UNM - Ichsani Ichsani; Andi Atssam Mappanyukki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Increasing the achievements of the futsal sports branch is a matter that has long been a problem, so Indonesia's futsal achievements have not been able to excel at the Asian and International levels. The limited knowledge and insights of national coaches about the regulation of training forms, causes the quality of athletes to be less developed as desired. The trainers should pay attention to some research results, especially those related to the sports that are trained. Seeing the condition of futsal sports, it cannot be denied that futsal sports are not like other sports, especially now that futsal is one of the sports in which regional development has priority. The method used in this activity was lecture and question and answer and field practice carried out during the three days of the activity. This activity is very useful for students because it is able to provide the latest information in futsal regulations. The participants realized that this activity was able to provide additional knowledge about futsal sports. Suggestions given with this activity are expected to the local bureaucracy especially FIK UNM and IKOR Study Program to send student representatives in each training activity, and futsal arbitration.